PENGARUH KECERDASAN SPIRITUAL DN MOTIVASI BELAJAR TERHADAP KEDISIPLINAN SISWA DI MADRASAH ALIYAH PONDOK PESANTREN SYAFA’ATURRASUL TELUK KUANTAN - Fitri, Dina; Zaitun, Zaitun; Yeli, Salmaini (LPPM UM Metro, 2025)
This study aims to examine the effect of spiritual intelligence on learning motivation and its impact on student discipline at MAS PP Syafa’aturrasul. This research uses a quantitative approach with a correlational design. The population consists of all students at MAS PP Syafa’aturrasul Teluk Kuantan, totaling 232 students. The sample for this study includes 128 students from grades X and XI. Data collection techniques use questionnaires and documentation. Data analysis techniques involve simple linear regression and multiple linear regression. The results of this study are: First, the level of student discipline at MAS PP Syafa’aturrasul is categorized as moderate at 36.7% and high at 63.3%. , there is a significant influence of spiritual intelligence on student discipline at MAS PP Syafa’aturrasul with an R-square value of 0.123. Second, there is a significant influence of learning motivation on student discipline at MAS PP Syafa’aturrasul Teluk Kuantan with an R-square value of 0.204. Third, here is a significant influence of spiritual intelligence and learning motivation simultaneously on student discipline at MAS PP Syafa’aturrasul Teluk Kuantan with an R-square value of 0.209. Keywords: Spiritual Intelligence, Learning Motivation, Discipline